2022
DOI: 10.21037/atm-22-3872
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of corrective effect of infraorbital depression by fat granule auto-transplantation via oral mucosa incision

Abstract: Background: Moderate facial depression is an important manifestation of aging, and traditional fat grafting is filled through the skin approach, and there may be damage to the terminal branch of the surface artery, thereby increasing the risk of fat embolism, so there is a safety implication. Therefore, a safe and effective filling pathway is a key point in the study of facial fat grafting in the suborbital area. Based on the results of anatomical research, this study looks for the filling level of non-well-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Also, in terms of nanofat, Khlosy and Abouarab (9) have demonstrated that 8 patients (80%) were satisfied, while 2 cases (20%) were not. In addition, Guo et al (17) conducted their study on 107 cases with depressions in the sub-orbital area and facial asymmetry, necessitating fat injection. All cases were followed for 6 -24 months, 67.3% of cases rated the results as "very satisfied", 29.0% rated as "satisfied", 3.7% rated as "average", and none of cases rated as "not-satisfied".…”
Section: Discussionmentioning
confidence: 99%
“…Also, in terms of nanofat, Khlosy and Abouarab (9) have demonstrated that 8 patients (80%) were satisfied, while 2 cases (20%) were not. In addition, Guo et al (17) conducted their study on 107 cases with depressions in the sub-orbital area and facial asymmetry, necessitating fat injection. All cases were followed for 6 -24 months, 67.3% of cases rated the results as "very satisfied", 29.0% rated as "satisfied", 3.7% rated as "average", and none of cases rated as "not-satisfied".…”
Section: Discussionmentioning
confidence: 99%